An exploratory study on the usage of Management Accounting Practices among Small and Medium Enterprises in Zimbabwe.: Array - Dlamini, Banele; Schutte, Danie P (The Journal of Accounting and Management, 2021)
The study explored the use of Management Accounting Practices (MAPs) by Small and Medium Enterprises (SMEs) operating in Zimbabwe as there is paltry research-based knowledge on the extent of their use. The study adopted an exploratory qualitative research approach following the interpretivist paradigm using a semi-structured interview for data collection from eighty-eight participants and utilizing content analysis. The study revealed that there is generally a low adoption of MAPs though there is relatively a high usage of traditional MAPs as compared to contemporary MAPs among SMEs in Zimbabwe. The study concludes that the failure of SMEs lies in the low utilization of MAPs, therefore it recommends that SMEs should increase the uptake of both traditional and contemporary MAPs as these techniques are not only essential for promoting success and survival of SMEs but they also create value for the entity. The Zimbabwean government and other stakeholders should also promote the usage of MAPs among SMEs as this will improve economic development. The usage of MAPs plays a pivotal role in the success of an entity in the modern globalised business. The study highly recommends the development of a management accounting framework for SMEs as it might affluence the application of MAPs among these small businesses.